Prepositional cases in Czech: toward a typological change - Bláha, Ondřej (Slavia Occidentalis, 2022)
This article examines the increase in frequency of use of the prepositional noun cases in Czech over the last three decades (1990-2019). The author has based his research on the Czech National Corpus where he created five temporally defined subcorpora containing only journalistic texts from the major Czech daily newspapers. Over the period under study, the share of prepositional cases in the total noun tokens has increased from 26.44% to 28.08% (by 1.64%). The share of cases with proper prepositions has increased the most, while the number of cases with improper prepositions has increased less. The author has identified developmental trends for specific frequented prepositions. According to the author, the increase in the frequency of prepositional cases in Czech is a phenomenon rooted in the “typological dispositions” of the Czech language. However, he considers the stylistic factor (the desire for more explicit, precise expression) to be a factor of more importance, contributing to the increase in the frequency of prepositional cases. On the other hand, some changes in the frequency of use of specific cases, most notably the observed greater frequency of the accusative (+2.21%), is a purely typologically motivated developmental change.